2017
DOI: 10.1371/journal.pone.0182851
|View full text |Cite
|
Sign up to set email alerts
|

Rac2 is required for alternative macrophage activation and bleomycin induced pulmonary fibrosis; a macrophage autonomous phenotype

Abstract: Idiopathic pulmonary fibrosis (IPF) is a chronic lung disease characterized by cellular phenotype alterations and deposition of extracellular matrix proteins. The alternative activation of macrophages in the lungs has been associated as a major factor promoting pulmonary fibrosis, however the mechanisms underlying this phenomenon are poorly understood. In the present study, we have defined a molecular mechanism by which signals transmitted from the extracellular matrix via the α4β1 integrin lead to the activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…Gong and his team found that excretory secretion of antigen (ES) from Schistosoma japonicum eggs can activate macrophages to exhibit enhanced M2b polarization [47]. It has been reported that reducing or even eliminating mice macrophages can reduce organ fibrosis [52, 53], while M2 macrophage adoptive transplantation can aggravate organ fibrosis in mice [54, 55]. Moreover, the decrease in the infiltration of M2 macrophages can be observed in the CHOP −/− animal fibrosis model [18, 56, 57].…”
Section: Discussionmentioning
confidence: 99%
“…Gong and his team found that excretory secretion of antigen (ES) from Schistosoma japonicum eggs can activate macrophages to exhibit enhanced M2b polarization [47]. It has been reported that reducing or even eliminating mice macrophages can reduce organ fibrosis [52, 53], while M2 macrophage adoptive transplantation can aggravate organ fibrosis in mice [54, 55]. Moreover, the decrease in the infiltration of M2 macrophages can be observed in the CHOP −/− animal fibrosis model [18, 56, 57].…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that small GTPase Rac controls the polarization of M2 macrophages 23,24. Signals transmitted from the extracellular matrix via the α4β1-integrin lead to the activation of Rac which regulates alternative macrophage differentiation into M2 phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in the tumor microenvironment, interstitial flow through the integrin β1 promotes autophosphorylation of FAK, which activates downstream Src/Akt, and transmits the signal to STAT3/6, thus promoting the M2-type polarization of macrophages (Li et al, 2018). In the pulmonary fibrosis model, the extracellular matrix via the α4β1 integrin leads to the activation of Rac2 and potentially regulates macrophage M2 differentiation (Joshi et al, 2017). In the colitis model, the Integrin αVβ3 polarized macrophages toward M1-type by promoting the overactivation of STAT1/3 downstream of the ILK/Akt/mTOR signaling pathway (Piedra-Quintero et al, 2019).…”
Section: Mechanism Discussionmentioning
confidence: 99%